Facilitation of noradrenaline release by adenosine A(2A) receptors in the epididymal portion and adenosine A(2B) receptors in the prostatic portion of the rat vas deferens - Queiroz, G (2002)
The adenosine-receptor modulation of noradrenaline release was compared in prostatic and epididymal portions of rat vas deferens. In both portions, tritium overflow elicited by electrical stimulation (100 pulses/8 Hz) was reduced by the adenosine A(1) receptor agonist, N-6-cyclopentyladenosine, and enhanced by the nonselective receptor agonist, 5'-N-ethylcarboxamidoadenosine, in the presence of the adenosine A(1) receptor antagonist, 1,3-dipropyl-8-cyclopentyl-1,3-dipropylxanthine (DPCPX; 20 and 100 nM). The adenosine A(2A) receptor agonist, 2-p-(2-carboxyethyl)phenethyl-amino-5'-N-ethylcarboxamidoadenosine, increased tritium overflow, but only in the epididymal portion. The enhancement caused by NECA was prevented by the adenosine A(2A) receptor antagonist, 4-(2-[7-amino-2-(2-furyl)[1,2,4]triazolo-[2,3-a][1,3,5]triazin-5-ylamino]ethyl)phenol (ZM 241385; 20 nM), in the epididymal and by the adenosine A(2B) receptor antagonist, alloxazine (1 muM), in the prostatic portion. Inhibition of adenosine uptake enhanced tritium overflow in both portions, an effect blocked by ZM 241385 in the epididymal and by alloxazine in the prostatic portion. The results indicate that adenosine exerts an adenosine A(1) receptor-mediated inhibition, in both portions, and facilitation mediated by adenosine A(2A) receptors in the epididymal and by A(2B) receptors in the prostatic portion.